Discogenic cell transplantation directly from a cryopreserved state in an induced intervertebral disc degeneration canine model. Issue 2 (11th May 2018) - Hiraishi, Syunsuke; Schol, Jordy; Sakai, Daisuke; Nukaga, Tadashi; Erickson, Isaac; Silverman, Lara; Foley, Kevin; Watanabe, Masahiko
Abstract : A multitude of studies has indicated the potential of cell therapy as a method for intervertebral disc (IVD) regeneration. Transplantation of a variety of cells has been assessed and shown capable of deterring the rate of degeneration in animal models and in human clinical trials. In this study, a novel approach using human discogenic nucleus pulposus cells directly from their cryopreserved state was assessed. In an established canine disc degeneration model, the degeneration process was evaluated in IVDs receiving precultured discogenic cells, thawed‐only discogenic cells, and a saline sham injection after induction of degeneration. Degeneration progression was followed over time by the evaluation of the disc height index (DHI). Finally, after 12 weeks, the manipulated and control discs were explanted, histologically stained, and scored. Treated discs demonstrated retained DHI values for all treatment options. Histologic evaluations demonstrated significant improvement of matrix features compared to the sham. Moreover, thawed‐only cells function at least as well as precultured discogenic cells. In short, cell transplantation of human discogenic cells directly from their cryopreserved state can arrest disc height degeneration and maintain histological matrix features in a canine disc degeneration model. The presented work demonstrates the potential of an off‐the‐shelf cell therapy product to treat degenerative disc disease. Abstract : Transplantation of human discogenic nucleus pulposus cells directly from their cryopreserved storage condition (off‐the‐shelf) were assessed and compared to identical cells following contemporary pre‐culture conditions, in a canine IVD degeneration model. 12‐weeks post transplantation the treated IVDs showed maintenance of IVD features (histologically and radiographically), with a trend of enhanced outcomes for the off‐the‐shelf treatment. Our data suggests off‐the‐shelf transplantation to be a safe and an effective strategy for IVD targeted regenerative therapies.